Trade and terroir: The political economy of the world's first geographical indications - Giulia Meloni; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2018)
The world's first geographical indications (GIs) were in the wine sector and focused on the delineation of the location of production, the "terroir": the Burgundy wines in the fifteenth century, the Port wines and Chianti wines in the eighteenth century, and the Champagne wines in the early twentieth century. We analyze the causes for the introduction of these GIs ("terroirs") and for changes in their delineation (expansion) later on. Our analysis shows that trade played a very important role in the creation of the "terroirs" but not always through the same mechanisms. For the Port and Chianti GIs it was exports to Britain that were crucial; for Burgundy it was domestic trade to Paris; and for the Champagne GI it was not exports but pressure from wine imports and new wine regions that played a crucial role. For the expansions of the GIs later in history, other factors seem to have been equally important. Expansions of the GIs in the years and centuries after their introduction followed major changes in political power; the spread of a new philosophy in liberal and free markets across Europe; and infrastructure investments which opened up markets and made exports cheaper from "new" producers.
Keywords: 330